The effect of masseter muscle strength on mandibular cortical bone thickness - Sianturi, Intan Permata Sari; Sumantri, Dominica Dian Saraswati; Wibisono, Jane Amelia Vebriani (Ikatan Radiologi Kedokteran Gigi Indonesia, 2026)
Objectives: The purpose of this study is to see the effect of the strength of the masticatory muscle (masseter muscle) on the thickness of the mandibular cortical bone. Materials and Methods: The method of this study is a correlational research design. Sampling was conducted using a consecutive sampling method with a population of 50 patients aged 20-44 years at RSGM Maranatha Bandung who had panoramic radiography according to the inclusion and exclusion criteria during the period of March to May 2024. Results: The results of this study involving 50 patients demonstrated a statistically significant correlation between masseter muscle strength and mandibular cortical bone thickness, with a correlation value of 35.16%. Based on the Pearson correlation test, the correlation coefficient was r = 0.593, indicating a moderate positive association. The maximum value of masseter muscle strength was 1.283 millivolts, while the minimum value was 0.00005 millivolts. The maximum mandibular cortical bone thickness value was 0.43, and the minimum value was 0.21. Conclusion: This study shows that there is an effect of masseter muscle strength on mandibular cortical bone thickness. Keywords: Masseter muscle, mandibular cortical bone, surface electromyography, panoramic radiography